Higher Education as a Field of Research in the Portuguese Speaking Countries: Insights on an Emerging Scientifc Field - Langa, Patricio (International Journal of African Higher Education, 2018)
This article examines the preconditions for the emergence of higher education as a feld of research in the Portuguese speaking countries. It uses various sources of data, including the worldwide inventory on higher education by the Center for International Higher Education of Boston College, to map the existing infrastructure for the establishment of higher education as new scientifc feld. This includes research centres, academic programmes, journals, and professional and academic associations. The article shows that higher education has become a complex social institution, which, according to Altbach (2014), is the condition that leads to the constitution of a new scientifc feld. Bourdieu’s theory of feld is used to shed light on the sociological conditions for the establishment of new felds. The article concludes that the prerequisites for an emerging feld of higher education research in the Portuguese speaking countries are in place, but further research is required to establish whether the magnet eﬀects of a functioning feld have been ignited. Cet article examine les conditions pour l’émergence de l’enseignement supérieur comme discipline de recherche dans les pays lusophones. Il utilise des sources variées pour schématiser les infrastructures nécessaires à l’institution de l’enseignement supérieur comme nouvelle discipline scientifque, y compris l’inventaire mondial sur l’enseignement supérieur du Center for International Higher Education à Boston College. Celui-ci inclut les centres de recherche, les programmes universitaires, les journaux, et les associations professionnelles et académiques. Cet article démontre que l’enseignement supérieur est devenu une institution sociale complexe, ce qui, d’après Altbach (2014), est la condition qui mène à la constitution d’une nouvelle discipline scientifque. En conclusion, cet article afrme que les prérequis à l’émergence d’une discipline de recherche sur l’enseignement supérieur dans les pays lusophones sont remplis, mais il faudrait eﬀectuer plus de travaux de recherche pour vérifer que les eﬀets magnétiques nécessaires au bon fonctionnement d’une discipline de recherche ont bien été enclenchés.